Pengaruh Perbaikan Tanah dengan Menggunakan Metode Grouting Semen terhadap Daya Dukung Pasir Lepas - Wulandari, Wulandari; Andriani; Hakam, Abdul (Syntax Corporation, 2023)
The city of Padang as the capital city of West Sumatra Province has a coastal area consisting of a layer of sandy soil until depth of 32 m. One of these coastal areas is the Jambak sand beach area, Padang. Sandy soil in loose condition has low shear strength, so it is necessary to improve the soil to increase strength sn’l. In this study the ground improvement technique used was grouting, the grouting materials used were cement and water with a ratio of 1:2. Grouting is carried out at a depth of 50 cm with a certain pressure (2 Psi), and curing for 7 days. The main purpose of grouting is to produce soil or rock that is stronger, denser and less permeable, to fill voids that may not be accessible without a certain amount of pressure. To obtain soil classification in the field, sondir tests were carried out before and after grouting. The results showed the was an increase in the bearing strength of the sandy soil as a result of injecting cement into the soil in the holes, seen in holes 1 and 2 with qc values ranging from 50-55 kg/cm2 at 1D distance and it was seen that the qc values decreased as the sondir point got further away from the grouting column, there was an increase in the qc value at 1D distance of around 2.5-2.75 times the control qc value on the 7th day after grouting. The qc value decreases when the sondir point is far from the grouting point.